Predictors of Career Success Among Lodging Revenue Managers: Investigating Roles of Proactive Work Behaviors. Issue 4 (2nd October 2017) - Cha, JaeMin; Kim, SeungHyun "James"; Beck, Jeff; Knutson, Bonnie J.
ABSTRACT: This study integrated the growing literature of proactive work behavior with career success among lodging revenue managers. Proactive work behavior is a timely, relevant, and important research topic for today's workplaces in the hospitality industry. The aim of this research was to test a model for linkage among four dimensions of proactive work behavior and career success, among 280 lodging revenue managers, while controlling for work experience, age, and gender. First, the confirmatory factor analyses examined the measurement models of proactive work behavior and career success. Next, hierarchical regression analyses demonstrated that all four dimensions of proactive work behaviors contributed positively to subjective career success, but not objective (extrinsic) career success.